The Strength Proof Judgment in the Case Sue for Divorce in the Religious Court Klaten - Firda Imah Suryani (Trescode Green Organization, 2025)
A guess is an inference drawn by a law or judge from an eventthat can be observed to an event that cannot be generallyobserved. The issue discussed is the validity of presumptiveevidence as a result of testimony in divorce cases. Evidence thatsupports allegations is regulated in Article 173 HIR, Article 310Rbg, and Article 1915 of the Civil Code. This research is adescriptive normative legal study. The data used is secondarydata consisting of primary legal materials and secondary legalmaterials. The data collection method used was document andreading material analysis, the research tool was identified asDecision number 0556/Pdt.G/2024/PA.Klt, the analysismethod used was deductive syllogism. The strength of evidencein a statutory accusation is absolute, binding and decisive,while the strength of evidence in a judge's accusation isindependent evidence. In giving a decision in a divorce case, thejudge takes into account presumptive evidence based ontestimony presented by the Plaintiff. The judge agreed to theplaintiff's request to divorce their marriage.